Oxide Scale Mechanism and Prevention Measures of 660 MW Ultra - Supercritical Lignite Boiler - BAO Yong - zhi, SUN Yu - xi, HU Shan - wei (Cailiao Baohu)
With the rapid growth of China’s power demand, thermal power units are gradually developing to large - capacity, ultra - supercritical coal - fired units. However, the inner wall of some tubes on the steam side of the heated surface of boiler equipment and the main turbine valve, valve and main and reheated steam pipeline are oxidized by water vapor under high temperature, and the resulting oxide skin peels off and accumulates, which can easily cause pipe blockage, pipe burst and other hazards, thus affecting the safe operation of the boiler. In this paper, the formation mechanism and the shedding mechanism of the oxide skin was analyzed deeply through literature review and experimental tests. Results showed that the rate of oxide scale formation was accelerated with the increase of pipe wall temperature and slowed down with the improvement of pipe oxidation resistance. The larger the difference between the linear expansion coefficient of the oxide scale and the metal body, the easier it was to cause the shedding of the oxide scale. Based on the above mechanism, the reasonable prevention measures of oxide scale were proposed from four aspects including unit selection and design debugging, operation and maintenance, furnace water treatment, boiler control and was implemented in a 2×660 MW ultra - supercritical unit for nearly one year, in which no serious incidents of superheat and tube burst occurred at the high temperature heating surface, effectively improving the reliability and economy of boiler operation.